The Ah Receptor Regulates Growth Factor Expression in Head and Neck Squamous Cell Carcinoma Cell Lines - John, Kaarthik (Mol Carcinog, 2013)
Previous studies in head and neck squamous cell carcinoma (HNSCC) cell lines have revealed that the Ah receptor (AHR) plays a significant role in mediating the ‘aggressive’ phenotype of these cells, which includes enhanced inflammatory signaling (e.g. IL6) and migratory potential. Here we sought to identify putative novel targets of the AHR associated with enhanced tumor invasiveness. Global gene expression analysis identified a number of genes that are repressed upon treatment of OSC-19 or HN30 cells with an AHR antagonist. Three growth factors were targets of AHR activity; amphiregulin (AREG), epiregulin (EREG) and platelet-derived growth factor A (PDGFA) were repressed by an AHR antagonist and further examined. Quantitative PCR analysis, ELISA and siRNA-mediated knock down of AHR revealed an attenuation of basal and/or induced levels of expression of these growth factors in two HNSCC lines, following AHR antagonism. In silico analysis revealed that these growth factors possess dioxin-like response elements. Two other AHR ligands, 6-formylindolo[3,2-b]carbazole and benzo(a)pyrene also elicited similar responses. In conclusion, this study identified AREG, EREG and PDGFA as growth factor targets of AHR activity associated with metastatic phenotype of HNSCC cells, suggesting that attenuation of AHR activity may be a therapeutic strategy.